2015
DOI: 10.1118/1.4938066
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of respiratory motion measurement of 4D-MRI: A comparison between cine and sequential acquisition

Abstract: Purpose: The authors have recently developed a cine-mode T2*/T1-weighted 4D-MRI technique and a sequential-mode T2-weighted 4D-MRI technique for imaging respiratory motion. This study aims at investigating which 4D-MRI image acquisition mode, cine or sequential, provides more accurate measurement of organ motion during respiration. Methods: A 4D digital extended cardiac-torso (XCAT) human phantom with a hypothesized tumor was used to simulate the image acquisition and the 4D-MRI reconstruction. The respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…In comparison to other studies which utilize the XCAT for simulation studies [26,34], we demonstrated how differing patient physiology could influence tracking accuracy. For the 20 virtual patients studied, the heart rate was the most influential anatomical parameter affecting the tracking accuracy.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In comparison to other studies which utilize the XCAT for simulation studies [26,34], we demonstrated how differing patient physiology could influence tracking accuracy. For the 20 virtual patients studied, the heart rate was the most influential anatomical parameter affecting the tracking accuracy.…”
Section: Discussionmentioning
confidence: 72%
“…to simulate realistic cardiac MRI on a virtual patient cohort of 40 digital phantoms [23], for the modeling of regional heart defects caused by ischemia with incorporation of a finite-element model [24] and in respirationfocused modeling applications. The respiration-focused modeling applications include the verification of reproducible patient-specific diaphragm and chest motion traces for lung cancer radiotherapy [25], the validation of novel 4D-MRI techniques which image respiratory motion [26] and an analysis of audiovisual biofeedback and gating on thoracic-abdominal 4D computed tomography [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, prospective methods usually require a long total scan time and produce a low contrast resolution. 27,30,[32][33][34] In contrast, conventional retrospective 4D-MRI methods 29,35,36 utilize a sorting method based on respiratory surrogate signals thus, requiring much shorter imaging time. But, breathing variation remains in the reconstruction process, often resulting in considerable image artefacts (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, prospective imaging techniques 30,32,33 frequently require a long total scan time when breathing motion varies from breath to breath and the image quality can be highly subject to the size of the respiratory triggering window. 27,30,[32][33][34] On the other hand, retrospective image techniques 29,35,36 often suffer from considerable image artefacts (i.e. streak, duplicate, blurring and incompletion) due to breathing variation.…”
Section: Used a Bellows Belt;mentioning
confidence: 99%
“…Different strategies were investigated to improve the performance of the external surrogate, either making use of audio-visual biofeedback (To et al 2016b) or advanced sorting (Liu et al 2015, Liang et al 2016, Tryggestad et al 2013d, Du et al 2015. As previously mentioned however, the use of internal breathing surrogates directly extracted from the acquired 2D images has been shown to increase robustness in organ motion description with respect to external surrogates (Stemkens et al 2015, Liu et al 2016a, Li et al 2017. Two main methods based on navigator sequences (Von Siebenthal et al 2007, Tokuda et al 2008, Wachinger et al 2012 or image-derived approaches (Cai et al 2011, Fontana et al 2016, Paganelli et al 2015c, Liu et al 2014a, Hui et al 2016, van de Lindt et al 2018b, van de Lindt et al 2018a, Uh, Khan and Hua 2016 are reported in the literature, relying on the acquisition of a navigator for sorting data, or on the derivation of the information directly from the data itself, respectively.…”
Section: Respiratory-correlated (4d) Mrimentioning
confidence: 99%